Determinants of External Debt in Developing Countries - Khac Lich, Hoang; Tu, Duong Cam (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
This paper investigates the determinants of external debt in developing countries. By analyzing the fixed effect model, with the panel data of 50 countries during 1996-2015, it shows that external debt has been increasing dramatically. This is because of an increase in debt accumulation in the past, public investment and exchange rate. By contrast, the pace of economic growth, inflation and net exports decreases the external debt. Keywords External debt, government debt, public debt developing countries References [1] Maghyereh, A., “Equity markets integration in the Middle East region, unpublished paper”, Hashemite University (2003). [2] Awan, R., Anjum, A. and Rahim, S., Berensmann “An Econometric Analysis of Determinants of External Debt in Pakistan”, British Journal of Economics, Management & Trade, 5 (2015) 4, 382-391. [3] Iyoha, M., “An Econometric Analysis of External Debt and Economic Growth in SubSaharan African Countries in External Debt and Capital Flights in Sub-Saharan Africa”, Eds SI Ajayi and M. Khan. Washington, 2000. [4] Easterly, W., “How did heavily indebted poor countries become heavily indebted? Reviewing two decades of debt relief”, World Development, 30 (2002) 10, 1677-1696. [5] Osei, B., “Ghana: The Burden of Debt Service Payment Under Strcutural Adjustment”, African Economic Research Consortium Research Paper No. 33 (1995) (Nairobi: Initiative Publishers). [6] Chenery, H. B. & Strout, A. M., “Foreign assistance and economic development”, The American Economic Review, (1996). 679-733. [7] Bacha, E. L., “A three-gap model of foreign transfers and the GDP growth rate in developing countries”, Journal of Development Economics, 32 (1990) 2, 279-296. [8] Phan Thế Anh và cộng sự, “Nợ công ở Việt Nam, quá khứ, hiện tại và tương lai”, 2013. [9] CIEM, “Đầu tư công, nợ công và mức độ bền vững ngân sách ở Việt Nam”, thông tin chuyên đề, 5 (2013). [10] VEPR, “Những đặc điểm của nợ công Việt Nam”, bài thảo luận chính sách CS-10 (2015). [11] Eaton, J., & Gersovitz, M., “Debt with potential repudiation: Theoretical and empirical analysis." The Review of Economic Studies 48 (1981) 2, 289-309. [12] Hajivassiliou, V. A., “The external debt repayments problems of LDC's: An econometric model based on panel data”, Journal of Econometrics, 36 (1987) 1, 205-230. [13] Bittencourt, M., Determinants of government and external debt: Evidence from the young democracies of South America 341, 2013. [14] Al-Fawwaz, T.M., “Determinants of External Debt in Jordan: An Empirical Study (1990- 2014)”, International Business Research, 9 (2014) 7, 116-123. [15] Greenidge, K., Drakes, L. and Craigwell, R., “The external public debt in the Caribbean Community”, Journal of Policy Modeling, 32 (2010) 3, 418-431. [16] Waheed, A., “Determinants of External Debt: A Panel Data Analysis for Oil & Gas Exporting and Importing Countries”, International Journal of Economics and Financial Issues, 7 (2017) 1. [17] Ferraro, V., & Rosser, M., “Global debt and third world development”, In M. Klare & D. Thomas (Eds.), World Security: Challenges for a New Century. New York: St. Martin’s Press, (1994), 332-355. [18] Barungi, B., & Atingi, M.,“Growth and foreign debt: The Ugandan experience”, External debt and capital flight in sub-Saharan Africa (2000), 93-127. [19] Roodman, D., M., “Still waiting for the jubilee: Pragmatic solutions for the third world debt crisis”, Washington, DC: Worldwatch Institute, (2001). [20] Siddique, A., Selvanathan, E.A. and Selvanathan, S., “The impact of external debt on growth: Evidence from highly indebted poor countries”, Journal of Policy Modeling, 38 (2016) 5, 874 - 894. [21] Haggard, S. & Kaufman, R. R., “Introduction: institutions and economic adjustment”,The Politics of Economic Adjustment, (1992), 3-37. [22] Woo, J., “Economic, political, and institutional determinants of public deficits”, Journal of Public Economics, 87 (2005) 3, 387-426. [23] Tiruneh, M. W., “An empirical investigation into the determinants of external indebtedness”, University of Munich, Empirical Research Group, Munich and Institute of Slovak and World Economics Slovak Academy of Sciences, Bratislava, Slovakia (2004). [24] Alesina, A. & Tabellini, G., “Credibility and politics”, European Economic Review, 32 (1998) 2, 542-550. [25] Alesina, A. & Tabellini, G., “A positive theory of fiscal deficits and government debt”, The Review of Economic Studies, 57 (1990) 3, 403-414 [26] Craigwell, R., Rock, L., & Sealy, R., “On the Determination of the External Public Debt: The Case of Barbados”, Social and Economic Studies (1988), 137-150 [27] Greene, W., H., “Econometric Analysis”, 5th, Ed.. Upper Saddle River, NJ (2003).